Biomass composition of perennial grasses for biofuel production in North Dakota, USA. Issue 5 (September 2011) - Xue, Qingwu; Nyren, Paul E; Wang, Guojie; Eriksmoen, Eric; Bradbury, Gordon; Halverson, Mark; Aberle, Ezra; Nichols, Kris; Liebig, Mark
Background: Successful development of biofuels from biomass feedstocks depends on high yields and acceptable quality. We investigated the chemical composition of ten perennial grasses and mixtures across environments in North Dakota, USA. The contents of neutral detergent fiber (NDF), acid detergent fiber, acid detergent lignin (ADL), hemicellulose (HCE), cellulose (CE) and ash were determined.Results: Biomass chemical composition was affected by environment and species/mixtures, and their interaction. Biomass under drier conditions had higher NDF, ADL and HCE contents but lower CE contents. Tall and intermediate wheatgrass had higher NDF, acid detergent fiber and CE but lower ash contents than the other species and mixtures. Switchgrass and mixtures had higher HCE. Tall wheatgrass and Sunburst switchgrass had the lowest ADL content as compared with other species. Biomass with higher yield had higher cellulose content but lower ash content.Conclusion: Combined with higher yields, tall and intermediate wheatgrass and switchgrass had the optimal chemical compositions for biomass feedstocks production.